2021
DOI: 10.1111/jfpe.13951
|View full text |Cite
|
Sign up to set email alerts
|

Solubilization mechanism and structural properties of high‐denatured peanut protein treated by shearing

Abstract: High-denatured peanut protein (PP), which exhibited a surface structure dominated by hydrophobic groups due to the high temperature and pressure in oil extraction, was limited in application with poor hydration property. To improve the interaction between PP and water molecules, high-speed shearing homogenization (HSH) technique was used to depolymerize the aggregates. The results showed that the concentration of soluble protein was increased from 0.22 to 0.79 mg/mL at 15 min, followed by enhanced water holdin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…The contents of β-sheet and β-turn in ACP-treated PM were increased and then decreased, respectively, which indicated that ACP induced the rearrangement of β-structure and the formation of hydrogen bonds. These results were in agreement with the analysis of Yu et al (2022b). Meanwhile, the decrease of α-helix was attributed to its transformation to the β-sheet after ACP treatment.…”
Section: Secondary Structure Analysissupporting
confidence: 90%
See 3 more Smart Citations
“…The contents of β-sheet and β-turn in ACP-treated PM were increased and then decreased, respectively, which indicated that ACP induced the rearrangement of β-structure and the formation of hydrogen bonds. These results were in agreement with the analysis of Yu et al (2022b). Meanwhile, the decrease of α-helix was attributed to its transformation to the β-sheet after ACP treatment.…”
Section: Secondary Structure Analysissupporting
confidence: 90%
“…These reactions led to the rupture of hydrophobic bonds in proteins and the exposure of active sites in the protein core. Meanwhile, some hydrophilic groups were generated and bound to the PM surface, thereby allowing more water molecules to penetrate the core (Yu et al ., 2021b). Ekezie et al .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations